Implementation Physical Test Results Measurement in Athletics Short Distance Running Using Application - Saputri, Wanda Marthin; Hartati, Hartati; Yusfi, Herri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The research titled "Implementation of Physical Fitness Test Results Measurement in Athletics Sports Branch - Short Running Event Using Applications in Students of SD Negeri 139 Palembang." This study aims to assess the physical conditions of SD Negeri 139 Palembang students through the utilization of applications. The research employed a quantitative descriptive method. The findings revealed that the physical conditions of SD Negeri 139 Palembang students were categorized as very good (0%), good (0%), sufficient (83%), less (17% with a frequency of 5), and very less (0%). In summary, the overall physical condition of students in SD Negeri 139 Palembang falls within the sufficient category with a percentage of 83%. The implications of this study emphasize the importance of raising awareness among students to consistently enhance and maintain their physical well-being, both within the community and at all times. This effort is aimed at improving the physical conditions of students categorized as sufficient, less, and very less, thereby promoting overall well-being.